Psychological Construction and Cultivation of New Entrepreneurs Using Industrial Cluster Theory and Multidimensional Structure Model - Fan, Huiling (Frontiers in Psychology, 2021)
The purpose is to analyze the influencing factors and training plans of cultivating new entrepreneurs in the new era based on industrial cluster theory. First, the status of the research on the correlation between psychological characteristics and entrepreneurial performance of new entrepreneurs is reviewed. Second, 200 new entrepreneurs in Xi'an City of Shaanxi Province are randomly selected as the research objects. And an empirical model of the correlation between entrepreneurial psychological characteristics and entrepreneurial performance is innovatively proposed. Finally, the questionnaire data are analyzed by correlation analysis and SPPSS26.0 statistical analysis. The results show that most of the entrepreneurs are between 30-50 years old, with a larger number of males, and most graduate from junior colleges. The gender and education level of the new entrepreneurs have little impact on their entrepreneurial performance (P > 0.05), while their age has a significant impact on their entrepreneurial performance (P<0.05). Moreover, there is a significant correlation between the entrepreneur’s psychological characteristics and the two dimensions of entrepreneurial performance (development and profitability) (P < 0.05). This shows that the key to cultivating new entrepreneurs is to develop their age and psychological characteristics, which can enhance the entrepreneurial ability of new entrepreneurs and provide a basis for cultivating multidimensional entrepreneurial talents in new enterprises.